Implementasi Nilai-nilai Karakter Islam Berbasis Pembiasaan Siswa di Madrasah Tsanawiyah Negeri Kota Batu - Rahim, Abdan; Setiawan, Agus (Program Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
This research aims to uncover the implementation of habituation method in Islamic education for the formation students character values at MTsN Batu, with sub focus includes: (1) a form implementation of habituation method in Islamic education for the formation students character values at MTsN Batu. (2) any characters that are formed on a student through a habituation method in Islamic education at MTsN Batu. (3) evaluation the implementation of habituation method in Islamic Education for the formation students character values at MTsN Batu. This study uses qualitative methods to do a descriptive approach. Checking the validity of the data is carried out by means of Triangulation and reference materials. While the principal Informant of this research is the head master of school, deputy head of student management, master of class, and other related parties in this research. The results of this research indicate that: a form implementation of habituation method in Islamic education for the formation students character values at MTsN Batu are: (1) Habituation of character, habituation in worship, and habituation in the annual event. (2) the resulting charactersÂ of the students through habituation methods in Islamic education at MTsN Batu are: Culture religious, communicative/ amicable, care of environment, discipline, creative, the spirit of nationality, an avid reader, social care, and responsibility. (3) evaluation the implementation of habituation method in Islamic education for the formation students character values at MTsN Batu are: the ceremony on Monday, the assembly of the council of teachers (meeting), and through the book TATIBSI (the student code of conduct) with assessment scores and calculated each semester.